(untitled) (Comparatismi, 2025)
Since the mid-20th century, literary criticism has been developed not only in books and articles that declare this purpose but also through discursive genres that assume criticism without declaring it. The critical function is then established in discourses that, when dealing with other texts, maintain relationships with them that range from the desire for continuity to the vocation of judgment, passing through the attempt to reorder discursive systems. The proposal aims to address discursive variants identified as prologue, chronicle, private diary, and epistolary, when their objective is to continue, justify, or polemicize with a text, thus converting the discourse itself into a vehicle for establishing values and operational concepts, judging authors and works, revising the canon. This article focuses on the chronicle based on the contributions of María Moreno.